2023
DOI: 10.1371/journal.pone.0283691
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of bovine schistosomiasis and associated risk factors in Ethiopia: A systematic review with meta-analysis of published articles, 2008–2018

Melkie Dagnaw,
Bihonegn Wodajnew,
Tsegaw Fentie
et al.

Abstract: Schistosomiasis is a tropical and subtropical parasitic infection that affects both animals and humans. It’s caused by the Schistosoma genus and spreads via snails as an intermediate host. Schistosoma bovis is widely spread in Ethiopia’s Northern, Eastern, Southwestern, and Central regions. It is an economically significant cattle disease with global health implications. Despite numerous prevalence studies of bovine schistosomiasis in different regions of the country, no systematic review and meta-analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…According to the present investigation, bovine schistosomiasis is recognized as a significant livestock ailment in and around Haramaya Town. In terms of coprological examination, the overall prevalence in the current study was comparable to that in studies conducted by, 29 who reported a pooled prevalence (24%) through meta-analysis in Ethiopia. The prevalence rates reported by 16,[30][31][32][33][34][35][36] are in line with the prevalence observed in our study.…”
Section: Discussionsupporting
confidence: 82%
“…According to the present investigation, bovine schistosomiasis is recognized as a significant livestock ailment in and around Haramaya Town. In terms of coprological examination, the overall prevalence in the current study was comparable to that in studies conducted by, 29 who reported a pooled prevalence (24%) through meta-analysis in Ethiopia. The prevalence rates reported by 16,[30][31][32][33][34][35][36] are in line with the prevalence observed in our study.…”
Section: Discussionsupporting
confidence: 82%